Answer:
-2(a+b)=-2a-2b
Equation is alway true
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
-2*(a+b)-(-2*a-2*b)=0
Step by step solution :
Step 1 :
Equation at the end of step 1 :
(0 - 2 • (a + b)) - (-2a - 2b) = 0
Step 2 :
Equation at the end of step 2 :
0 = 0
Step 3 :
Equations which are always true :
3.1 Solve 0 = 0This equation is a tautology (Something which is always true)
Equation is alway true
Step-by-step explanation: